Conformational transitions in CD4 due to complexation with HIV envelope glycoprotein gp120. - Denisova, G; Raviv, D; Mondor, I; Sattentau, Q; Gershoni, J (1997)
The binding of the surface envelope glycoprotein gp120 to its receptor, CD4, has been well characterized and is the primary basis for the cell tropism of HIV. In this study, the interaction between recombinant soluble CD4 and native membrane-associated CD4 with gp120 is probed by the use of mAbs. Complexation of gp120 with both forms of CD4 induces conformational epitopes that can be defined with specific mAbs. CG1, CG7, and CG8 are three novel mAbs that have a distinct preference for CD4 complexed over noncomplexed with gp120. The epitopes of these unique mAbs were mapped by cross-inhibition with previously characterized mAbs to a region encompassing the CDR2 and CDR3 loops in domain 1 of CD4. Systematic analysis of CG mAbs binding to CD4 and CD4/gp120 complex delineates a region in the D1 domain of CD4 that undergoes conformational rearrangements upon gp120 binding to its receptor.